Odpowiedzi

2010-04-08T14:53:03+02:00
2/5 (3 - x) = - 2 |*5
2(3-x)=-10
6-2x=-10
-2x=-10-6
-2x=-16 |:(-2)
x=8

3/4 ( 2 - 3x) = - 6 |*4
3(2-3x)=-24
6-9x=-24
-9x=-24-6 |:(-9)
x=30/9
x=3 1/3

1/5 ( x - 3) = 9 - x |*5
x-3=45-5x
x+5x=45+3
6x=48 |:6
x=8

0,6+x/2 = x+1 |*2
1,2+x=2x+2
x-2x=2-1,2
-x=0,8 |*(-1)
x=-0,8

a) 2(x+3)=10
2x+6=10
2x=10-6
2x=4 |:2
x=2

b) tu była jakaś pomyłka, albo brakowało nawiasu, albo zamiast 0 miał być nawias
3(x-10)+2=8
3x-30=8-2
3x=6+30
3x=36 |:3
x=12

czy taki
3(x-1)+2=8
3x-3=8-2
3x=6+3 |:3
x=3

c) 2(13 - x)-9=1
26-2x=1+9
-2x=10-26
-2x=-36 |:(-2)
x=18

d) 3(1-x)+2=-7
3-3x=-7-2
-3x=-9-3 |:(-3)
x=4

e) 3(x+3)=2(x+4)+x+1
3x+9=2x+8+x+1
3x-2x-x=9-9
0=0
równanie tożsamościowe

f) 4(3x+2)+5(2x+3)=-(2x+13)
12x+8+10x+15=-2x-13
12x+10x+2x=-13-8-15
24x=-36 |:24
x=-1 1/2

g) 4(x-2)-2(x-4)=5(x+1) - 3x
4x-8-2x+8=5x+5-3x
2x-2x=5
0=5
równanie sprzeczne

h) 2(x-4)=(2x-1) + 6 (x+1)
2x-8=2x-1+6x+6
2x-2x-6x=5+8
-6x=13 |:(-6)
x=-13/6
x=-2 1/6